2009
DOI: 10.1242/jcs.039552
|View full text |Cite
|
Sign up to set email alerts
|

PP2A regulates BMP signalling by interacting with BMP receptor complexes and by dephosphorylating both the C-terminus and the linker region of Smad1

Abstract: Phosphorylation of Smads is a crucial regulatory step in the signal transduction pathway initiated by bone morphogenetic proteins (BMPs). Although the dephosphorylation events terminating the pathway in the nucleus have been characterized, little is known about the dephosphorylation of Smads in the cytoplasm. In a proteomic screen for proteins interacting with the BMP type-II receptor, we found the regulatory Bβ subunit of PP2A. PP2A is one of the major serine/threonine phosphatases involved in cell-cycle regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 69 publications
(99 reference statements)
1
39
0
Order By: Relevance
“…In vertebrates, the PPP2R2A and PPP2R2D subunits were shown to regulate TGF-␤/Activin/Nodal signaling in opposite ways (46), PPP2R2A enhancing signals by stabilizing ACVR1B and TGFBR1 basal levels, whereas PPP2R2D restricted receptor activity. Our data imply that the PPP2R2B subunit interacts preferentially with ACVRL1, and independently of its kinase activity, as previously reported for BMPR2 (47). We also confirm that BMPR2 and TGFBR2 associate with PPP2R2B and PPP2R2D.…”
Section: Discussionsupporting
confidence: 90%
“…In vertebrates, the PPP2R2A and PPP2R2D subunits were shown to regulate TGF-␤/Activin/Nodal signaling in opposite ways (46), PPP2R2A enhancing signals by stabilizing ACVR1B and TGFBR1 basal levels, whereas PPP2R2D restricted receptor activity. Our data imply that the PPP2R2B subunit interacts preferentially with ACVRL1, and independently of its kinase activity, as previously reported for BMPR2 (47). We also confirm that BMPR2 and TGFBR2 associate with PPP2R2B and PPP2R2D.…”
Section: Discussionsupporting
confidence: 90%
“…BMP and TGF-␤ signaling are regulated by SCP1-3 phosphatases, which target the C-terminal phosphorylation of Smad1 and the linker phosphorylation of Smad2 and -3 (38,39). BMP receptor associates with one form of PP2A leading to dephosphorylation of BMP R-Smad, Smad1, in normoxia, and different PP2A forms can dephosphorylate different receptors of the TGF-␤ superfamily and Smad1 (11,12). Bengtson et al (12) show that PP2A dephosphorylates Smad1 linker region and only weakly the C terminus in normoxia.…”
Section: Discussionmentioning
confidence: 99%
“…BMP receptor associates with one form of PP2A leading to dephosphorylation of BMP R-Smad, Smad1, in normoxia, and different PP2A forms can dephosphorylate different receptors of the TGF-␤ superfamily and Smad1 (11,12). Bengtson et al (12) show that PP2A dephosphorylates Smad1 linker region and only weakly the C terminus in normoxia. They also reported that the linker region dephosphorylation leads to enhanced nuclear localization of Smad1 in normoxia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations